Space efficiency study on the physical configuration of highly visited offices in Metro Davao establishing architectural guidelines for front line service areas of local government agencies - Geyrozaga, Glea Czarina I. (2015)
The present situation of the offices in the locality of the Davao City is manifestations of poor space coordination or planning. It is a result of insufficiency of other factors such as finance and management coordination within office premise making architectural needs secondary of importance. However, the putting aside of Spatial importance within a building induced further log jam on processing services of respective offices leading to agitation on the end of the clients. This is the essence of the study. The study focused on articulating guidelines such that Space Efficiency, accurate for the offices was achieved. The researcher used the Fuzzy Logic Tool, processed by a Fuzzy Logic Simulator to gauge some spatial elements of offices that makes it ?efficient?. The simulation is framed under the Fuzzy Rules that contain the determinants of a standard office design. The Fuzzy Rules are in word form but each corresponding to a certain numerical weight in the simulator. With resulting rating of the individual floor of the respective offices, the template for the guideline was produced. This template was unified with their individual service processes and was applied to the proposed Government Complex design. The studied offices are redesigned with the application of the results of the study and simulated a second time to substantiate its efficiency. The entire concept of the proposed translation design was to incorporate these branch offices in one complex to (1) provide proximity of offices that are highly visited, endorsing a ?one-time-stop? for clients, (2) provide a commercial kiosk for subsidiary processes, e.g. photocopy, notarial services, rush I.D. printing, etc., (3) provide space efficiency on the interior of each building and of the exterior ? the surrounding utilities such as parking, drop-off areas, and even landscaping. Succinctly, the proposed design aimed coordination from site efficiency to the interior space efficiency of the offices entirely for the benefit of the users of the complex.